ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT BELI ULANG PRODUK SERTA DAMPAKNYA TERHADAP LOYALITAS PELANGGAN (STUDI KASUS PADA PRODUK SAKATONIK LIVER DI KOTA SEMARANG) - Iwan Kurniawan; Suryono Budi Santoso; Bambang Munas Dwiyanto (JURNAL STUDI MANAJEMEN ORGANISASI, 2012)
ABSTRACT The moving of business paradigm which is full of competition, the company is required to be always creative and innovative to get survive. So, in developing products, the company must have a qualified product, price leadership, and placed the position of the product in the market through promotion. The research data is found through questionnaire from 140 respondents. Then the data got is analyzed using Structural Equation Modeling (SEM) analysis technique. To do this analysis technique, there are seven steps that should be done, namely extended model on the basic of theory, extended plot diagram, plot diagram conversion into the equality, the choosing of input matrix and estimation technique, scoring identification of problem, evaluate criteria goodness of fit and interpretation and modification of model. The suitable full model result got using SEM analysis technique are Chi Square = 146.876, probability = 0.122, RMSEA = 0.033, GFI = 0.903, AGFI = 0.870, CMIN/DF = 1.147, TLI = 0.981, CFI = 0.984.. And the hypothesis tested is known that the product quality influenced toward repeat buying intention, promotion intensity influenced toward repeat buying intention, perceived price influenced toward repeat buying intention, and repeat buying intention influenced toward customer loyalty. Based on the research result, there are some managerial implications which can be used as a review. To increase the repeat buying intention can be done by doing promotion through arranged frequention, place and show time. Key words : product quality; promotion intensity; perceived price; repeat buying intention.